Fathers, Parental Leave and Gender Norms - Ulrike Unterhofer; Katharina Wrohlich (Institute of Labor Economics (IZA), 2017)
Social norms and attitudes towards gender roles have been shown to have a large effect on economic outcomes of men and women. Many countries have introduced policies that aim at changing gender stereotypes, for example fathers' quota in parental leave schemes. In this paper, we analyze whether the introduction of the fathers' quota in Germany in 2007, that caused a sharp increase in the take-up of parental leave by fathers, has changed the attitudes towards gender roles in the grandparents' generation. To this end, we exploit the quasi-experimental setting of the 2007 reform and compare grandparents whose son had a child born before the 2007 reform to grandparents whose son had a child born after it. Our results suggest that such policy programs not only induce direct behavioral responses by the target group but also have indirect effects on non-treated individuals through social interaction and can thus change attitudes towards gender roles in a society as a whole.
Keywords: J16; H31; J18; D13; J22; 330; parental leave; gender equality; social norms; social interaction; policy evaluation